2016
DOI: 10.1016/j.joen.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Status of Root-filled Teeth Restored with Composite, Amalgam, or Full Crown Restorations: A Cross-sectional Study of a Swedish Adult Population

Abstract: The results did not indicate any association between AP and resin composite restorations. Neither the type nor the material of the restoration was of significance for periapical status as long as the quality was adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
3
16
1
Order By: Relevance
“…A recent cross‐sectional study by Dawson et al investigated the prevalence of various restoration types in root‐filled teeth and the association to periapical disease in the Swedish adult population. 35% of the root‐filled teeth had a direct coronal restoration, 62.6% had an indirect coronal restoration and the remaining 2.4% had no restoration . In the present study we found a lower frequency of indirect restorations compared to the cross‐sectional study.…”
Section: Discussioncontrasting
confidence: 46%
“…A recent cross‐sectional study by Dawson et al investigated the prevalence of various restoration types in root‐filled teeth and the association to periapical disease in the Swedish adult population. 35% of the root‐filled teeth had a direct coronal restoration, 62.6% had an indirect coronal restoration and the remaining 2.4% had no restoration . In the present study we found a lower frequency of indirect restorations compared to the cross‐sectional study.…”
Section: Discussioncontrasting
confidence: 46%
“…In fact, higher success rates (94%) were found with teeth adequately restored using composite resin or amalgam. Dawson et al [ 44 ] reported no differences in AP frequencies between teeth adequately restored with amalgam, composite resin, or fabricated full-crowns (i.e., 29.7%, 43.1%, and 26.2%, resp.). An association was found between AP and inadequate root canal filling and marginal bone loss, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced digital periapical radiographs were used in this study rather than panoramic radiographs, which have been more commonly used in previous similar epidemiological studies,[ 17 18 27 28 ] are more readily available, and afford a more comprehensive overview of patients (a large volume of patient data could be readily gathered). Enhanced digital periapical radiographs have a higher sensitivity in detecting periapical osteolytic lesions, especially in the anterior region.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is inconsistent with the studies of Dawson et al . [ 27 ] and Nimigean et al . [ 37 ] In those investigations, the commonly used posts were cast posts (in 43.7% and 69.6% of cases, respectively), and threaded posts were used only in 30.4% and 5.8% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%